Pendampingan Manajemen Usaha Laundry Berbasis Tekonologi - Sunarmi, Sunarmi; Marthalena, Yenny; Utami, Tika Putri; Juliyana, Milan (Penerbit Goodwood, 2023)
Purpose: This mentoring program aims to help partners increase their business capacity through promotion and repair/addition of business equipment. Research Methodology: The partner in this program is Laundry Bunda, a business that was just started in September 2015 by the owners Sri Wahyuni and Henry Yudo Pranoto, located at Blok V No.5, Jl. Perum BKP, Kemiling Permai, Kec. Kemiling, Bandar Lampung City, Lampung 35152, Indonesia. The problems faced by partners include: 1) promotional activities are not yet optimal, 2) equipment is not adequate/not enough, and 3) business layouts are not well organized. To overcome these problems in this service program the activities that have been carried out are: Expanding the market and maximizing promotional media by: Making business signboards, making and distributing brochures, promoting through social media, giving discount cards to customers. Results: The results of this program are: 1) Laundry Bunda business has a bigger and more attractive signage; 2) partners have online promotion media on Instagram; 3) partners have online brochures through Imooji; 4) the presence of additional equipment and a neat and comfortable business layout Conclusions: Availability of partner awareness to optimize business promotion activities, Availability of promotional media both simple and promotional media on Instagram, Availability of partner awareness to maintain service quality, Availability of additional equipment which supports the laundry business process.